Tackling the Problem of Crops Supply Chain in Indonesia using Internet of Things Based on Law of the Farmers - Intan Soeparna (Universitas Airlangga, 2020)
One of the agricultural problems in Indonesia is the crops supply chain that hampers the ability of the farmers to achieve better income from their farming activities. Although the government has issued the Law of the Farmer No 19 the year 2013 to protect and empower the farmer, the problem is still prevalent. It leads to a question of how to implement the law to tackle the problem of the crops supply chain. The study explains that the government has issued an Economy Digital Policy to create electronic commerce in agribusiness (E-Agribusiness) for farmers and to solve their agribusiness problem. However, the use of electronic agribusiness is not yet ample to solve the problem of the crops supply chain. The solution is a suggestion to apply Internet of Things which is using RFID technology to solve the problem of crops supply chain and distribution in E- Agribusiness. The methodology of the study is the normative approach and literature review.